Epidemiology and mortality of pelvic and femur fractures—a nation- wide register study of 417,840 fractures in Sweden across 16 years: diverging trends for potentially lethal fractures - Lundin, Natalie; Huttunen, Tuomas T; Enocson, Anders; Marcano , Alejandro I; Tsai, Li Felländer-; Berg, Hans E (Acta Orthopaedica, 2021)
Background and purpose — Fractures of the pelvis and femur are serious and potentially lethal injuries affecting primarily older, but also younger individuals. Long-term trends on incidence rates and mortality might diverge for these fractures, and few studies compare trends within a complete adult population. We investigated and compared incidence and mortality rates of pelvic, hip, femur shaft, and distal femur fractures in the Swedish adult population. Patients and methods — We analyzed data on all adult patients ≥ 18 years in Sweden with a pelvic, hip, femur shaft, or distal femur fracture, through the Swedish National Patient Register. The studied variables were fracture type, age, sex, and 1-year mortality. Results — While incidence rates for hip fracture decreased by 18% (from 280 to 229 per 105 person-years) from 2001 to 2016, incidence rates for pelvic fracture increased by 25% (from 64 to 80 per 105 person-years). Incidence rates for femur shaft and distal femur fracture remained stable at rates of 15 and 13 per 105 person-years respectively. 1-year mortality after hip fracture was 25%, i.e., higher than for pelvic, femur shaft, and distal femur fracture where mortality rates were 20–21%. Females had an almost 30% lower risk of death within 1 year after hip fracture compared with males. Interpretation — Trends on fracture incidence for pelvic and femur fractures diverged considerably in Sweden between 2001 and 2016. While incidence rates for femur fractures (hip, femur shaft, and distal femur) decreased or remained constant during the studied years, pelvic fracture incidence increased. Mortality rates were different between the fractures, with the highest mortality among patients with hip fracture.